Effects on print quality of varying acrylic binder types in water-based flexographic ink formulations - SÖNMEZ, SİNAN (My University, 2022)
The ink industry is one of the world\"s largest markets due to the increasing demand for printing inks for the packaging industry. Flexography printing is a well-known promising technology for large-area printing due to its high printing speed and roll-to-roll capability to print economically on a variety of surfaces and is used in nearly in all areas of packaging printing. Water-based inks are considered non-toxic, odourless, and more environmentally friendly options compared to solvent-based inks. Therefore, in this article, the goal was to develop new water-based ink formulation with different acrylic binders for flexographic printing on commercial solid bleached sulphate (SBS) board. Five inks were formulated with four different acrylic binders and compared to a commercially available ink to study their performance. The developed inks were investigated with regard to their print qualities and print characteristics. It was found that the binder type influenced some print quality while the effect was not significant for others. Using flexography printed cyan inks, the ink formulated with the highest molecular weight had the lowest print density and the largest tonal value increase (TVI) observed between 40 and 60 tone values. The same ink had the largest mottle values and variation in topography. For values of print contrast and delta gloss at 75 degrees, although differences were observed between average values, data had inconclusive variation and spread around averages, where no conclusive trends or effects of acrylic binder type on these response factors were observed. Print chroma and dot roundness results were equally close for all printed samples.
Keywords: Kimya Mühendisliği ve Teknolojisi; Tekstil Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Textile Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MÜHENDİSLİK, KİMYASAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); ENGINEERING, CHEMICAL; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Genel Malzeme Bilimi; Genel Mühendislik; Mühendislik (çeşitli); Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; General Materials Science; General Engineering; Engineering (miscellaneous); Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences